Reviews of Science for Science Librarians: Genome-Wide Association Studies (GWAS) - Jeong, Sarah H.; Kim, Seong-Tae (Science & technology libraries (New York, N.Y.), 2011)
Since the completion of the Human Genome Project and the International HapMap Project, genome-wide association studies (GWAS) have been undertaken to uncover associations between genetic variants and human diseases and traits. GWAS research is a step forward in biomedical research, and this article provides an overview of the history, study design, and significant achievements in the field. In addition, this article presents an annotated bibliography of reliable, core research resources including data repositories, research institutes, consortia, analytical tools, and bioethical issues related to GWAS, which can serve as a reference for librarians, graduate students, and scientific researchers who are interested in this research area.